Returnees' Identity Construction at a BA TESOL Program in Mexico - Rivas Rivas Leonardo (Universidad Nacional de Colombia, 2013)
This article has at its core the unraveling of factors that have influenced the identity of those who have been caught in between two worlds (Mexico and The United States) and whom will be called pre- and in-service returnees from now on. A qualitative approach was chosen in order to delve deep into the participants' lived experiences through narrative inquiry which in turn aided in the discovery of the elements that have influenced their identity construction. The data suggest that those same elements have been crucial in the creation of a small culture among the participants at a teacher education program in teaching English to speakers of other languages at a Mexican university. Este artículo se centra en aclarar algunos de los factores que influyen en la identidad de las personas que se han visto atrapadas entre dos "mundos" (México y Estados Unidos), también conocidas como los "retornados". Se optó por un método cualitativo para ahondar en sus experiencias vividas mediante la indagación narrativa, la cual a su vez aportó al descubrimiento de elementos que influyen en la construcción de sus identidades. Los datos sugieren que esos mismos elementos son de suma importancia en la constitución de una pequeña cultura dentro de la licenciatura en la enseñanza de inglés a hablantes de otras lenguas, en una universidad mexicana.